Pemanfaatan Kulit Pisang Kepok Kuning (Musa acuminata balbisiana) sebagai Bahan Baku Bioetanol Konteks Teknologi Ramah Lingkungan - Putri Ramadan Lazuardi; Ariefa Primair Yani; Rendy Wikrama Wardana; Mellyta Uliyandari; M. Syaipul Hayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the optimal composition and fermentation time by varying the starter used to make bioethanol. The method used was an experiment with 45 samples of yellow kepok banana peel which were fermented for 13, 19 and 25 days. This research used 5 treatments, namely, a) composition A, namely 100% yeast (no added nutrients); b) composition B, namely 100% urea; c) composition C, namely 100% NPK; d) composition D, namely 50% urea and 50% NPK; e) composition E, namely 75% urea and 25% NPK. The quantitative data obtained was then analyzed using the average bioethanol content presented in the table. Qualitative data was analyzed descriptively with a systematic study. The results showed that the highest bioethanol content was obtained after fermentation (12.67 ± 9.29%) and after distillation (32 ± 10%) with composition A (100% yeast) and a fermentation time of 25 days. The highest combination of bioethanol yields was obtained after fermentation (6 ± 0%) and after distillation (31.67 ± 2.31%) with composition E (75% urea and 25% NPK) with a fermentation time of 25 days. In conclusion, the longer the fermentation time, the more bioethanol content increases. Keywords: Bioethanol, Kepok Banana Peel, Environmentally Friendly Technology